Accuracy of immunochromatographic strip test in diagnosis of alpha-thalassemia-1 carrier - Chanane Wanapirak (2018)
Objective: To determine the accuracy of alpha-Thal Immunochromatographic (IC) strip in diagnosis of alpha-thalassemia 1 carrier among pregnant women, using PCR for alpha-thalassemia 1 (SEA type) as a gold standard. Material and Method: Asymptomatic pregnant women attending the antenatal care clinic were recruited. Their blood samples were taken for IC Strip Test (α Thal IC strip, i+Med Laboratories Company Limited) in predicting alpha-thalassemia 1 carrier and separately sent for PCR for diagnosis of α-thalassemia 1 carrier as a gold standard. Results: Four hundred ninety nine pregnant women were recruited into the present study at various gestational weeks. The accuracy of alpha-Thal IC strip test was relatively high as shown in Table 1. Of them, 62 cases were proven to be alphathalassemia 1 trait and all of them had the results of positive IC strip, giving a sensitivity of 100%. However, 45 pregnant women of non-α-thalassemia 1 trait had positive test, giving a specificity of 89%. Conclusion: The present study was solid evidence for clinical application of α-thal IC strip in screening program of thalassemia to reduce the need for PCR in diagnosis of α-thalassemia 1 carrier because of its very high sensitivity. The negative test reassures the non α-thalassemia 1 carrier status. Moreover, due to its simplicity, convenience to use, low cost, less-time consuming, clear interpretation and no need for either equipment or expensive laboratories, it may probably be very helpful in a massive screening program.